2011
DOI: 10.1653/024.094.0415
|View full text |Cite
|
Sign up to set email alerts
|

Plant Phenology-Related Shifts in Color Preferences ofEpicometis(Tropinota)Hirta(Coleoptera: Scarabaeidae: Cetoniinae) Adults - Key to Effective Population Monitoring and Suppression

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
8
1
3
Order By: Relevance
“…Many colors, yellow, fluorescent yellow, white, brown, transparent, chartreuse, coral, dodger blue, golden rod, hot pink, light sea green, light sky blue, medium orchid, etc have been evaluated to find out the most attractant colors for T. hirta in numerous scientific studies (Schmera et al, 2004;Kozár, 1972 . Some researchers declared that adults of T. hirta were strongly attracted to objects of light blue color (Kozár, 1972;Aydın, 2011) while some of them affirmed that the blue color has been the most attractive color for T. hirta (Tóth et al, 2005). Likewise some of the scientific study results showed that T. hirta had been attracted to yellow, light blue or white color in a field test, but they found no significant differences between colors (Schmera et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many colors, yellow, fluorescent yellow, white, brown, transparent, chartreuse, coral, dodger blue, golden rod, hot pink, light sea green, light sky blue, medium orchid, etc have been evaluated to find out the most attractant colors for T. hirta in numerous scientific studies (Schmera et al, 2004;Kozár, 1972 . Some researchers declared that adults of T. hirta were strongly attracted to objects of light blue color (Kozár, 1972;Aydın, 2011) while some of them affirmed that the blue color has been the most attractive color for T. hirta (Tóth et al, 2005). Likewise some of the scientific study results showed that T. hirta had been attracted to yellow, light blue or white color in a field test, but they found no significant differences between colors (Schmera et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Epicometis hirta is a polyphagus pest, being reported on 48 species of plants (Subchev et al, 2011). The damage is produced by adults which consume the reproductive organs of host flowers, such as orchard trees, cereals or ornamental plans (Aydin, 2011;Vuts et al, 2009). It's attack can diminish up to 70% of flowers in nurseries and young cherry orchards (Kutinkova and Andreev, 2004;Roşca et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Para A. cornifrons existe apenas um registro em São Paulo (Di Iorio, 2013 (Orozco, 2012;Di Iorio, 2013). Existem registros de ataques desta espécie a frutíferas e roseira (Garcia et al, 1993;Garcia & Corseuil, 1998/1999Cunha et al, 2007;Aydin, 2011) e também em plantações de milho na fase reprodutiva (Cunha et al, 2007). Micó et al (2000) descreveram o estágio larval desta espécie a partir do terceiro ínstar.…”
Section: Resultsunclassified
“…Hologymnetis undulata é a única espécie do gênero que se encontra na América do Sul (Ratcliffe & Deloya, 1992 (Ratcliffe, 2005;2011). Existe registro de I. bonplandi para o Pará, Minas Gerais e Rio de Janeiro e de M. maculosa para o Brasil (Di Iorio, 2013).…”
Section: Resultsunclassified
See 1 more Smart Citation